Empowering Adolescents to Make Healthy Choices: Effects of the Primero Module on Reproductive Health Literacy - Evagus Malinda; Tina Mawardika (CV. Global Health Science Group, 2026)
Adolescents are vulnerable to reproductive health problems due to rapid biological, psychological, and social changes, which may be exacerbated by low reproductive health literacy. This study aimed to examine the effect of the PRIMERO (Reproductive Education through Modules for Optimistic Youth Empowerment) module on adolescents’ reproductive health literacy. A quasi-experimental study with a pretest–posttest control group design was conducted among 34 adolescents aged 15 years, who were equally divided into an intervention group (n = 17) and a control group (n = 17). The intervention group received reproductive health education using the PRIMERO module, while the control group received conventional health education. Reproductive health literacy was measured before and after the intervention and analyzed using paired t-tests and independent t-tests. Data were collected using a reproductive health literacy questionnaire administered to adolescents twice, namely before and after the interventionThe results showed that the mean literacy score in the intervention group significantly increased from 194.59 to 215.06 (p = 0.032), whereas the control group showed no significant improvement, with mean scores increasing from 172.88 to 173.76 (p = 0.188). Furthermore, a significant difference in post-intervention literacy scores was found between the intervention and control groups (p = 0.001). These findings indicate that the PRIMERO module is effective in improving adolescents’ reproductive health literacy and can be used as an educational medium to support reproductive health promotion among adolescents.